Transforming Children's Character Education in Islamic Da'wah in the Era of Social Media - Nur'aena, Lia (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2023)
This paper examines the transformation of children's character education in Islamic da'wah within the era of social media. The main question addressed is how Islamic da'wah can adapt to effectively nurture children's moral development amidst rapid digitalization. Positioned within the framework of Islamic educational values, this study argues that conventional da'wah approaches must be integrated with innovative digital strategies. The discussion is conducted through a qualitative descriptive method, using literature review and analysis of contemporary digital practices. The main result indicates that effective Islamic character education today requires the use of creative, interactive, and value-based digital content, parental collaboration, and the development of positive online communities. These strategies ensure that Islamic values are meaningfully transmitted and internalized by children in their formative years despite the challenges posed by the social media environment.